Agility in Disaster Relief: A Social Construction Approach. Issue 2 (2nd February 2018) - Nelan, Mary M.; Wachtendorf, Tricia; Penta, Samantha
Abstract: The convergence of materiel donations following disaster events is well documented in the literature. This influx of goods is often dubbed a "second disaster" with non‐priority and unnecessary goods causing transportation and storage challenges to the community of survivors. Interviews were conducted following Hurricane Sandy in 2013 and two tornadoes outside of Oklahoma City in May 2013. Findings illustrate conflicting views about how to best achieve agility in disaster donation supply chains, although there was general agreement among interviewees that agility was desirable. From a broader perspective, the findings reveal that individuals involved in the supply chain differentially assign value in the donations process, including if they value donor needs over survivor needs, and hold different views on whether or not cash or goods are of greater value to the donors and survivors. Agility—the timing, flexibility, and reaction time in the supply chain—was viewed as necessary to a healthy supply chain; however, there was not a universal understanding of how to achieve an agile supply chain. This finding is consequential if relief operations hope to ultimately enhance agility in this process.